Snowflake Bentley - Martin, Jacqueline Briggs; local (Boston : Houghton Mifflin, 1998)
A biography of a self-taught scientist who photographed thousands of individual snowflakes in order to study their unique formations
School Library Journal
Booklist starred
Publisher's Weekly
.
Follett Library Resources
Caldecott 1999 Medal Winner
Keywords: K-3 -- (Wilson Alwyn), -- 1865-1931; Juvenile literature. -- Snowflakes; Juvenile literature. -- Nature photography; Juvenile literature. -- Meteorologists -- United States -- Biography; Juvenile literature. -- Photographers -- United States -- Biography; Juvenile literature. -- (Wilson Alwyn); 1865-1931.; Scientists; Snow. -- (Wilson Alwyn); sears -- Scientists; sears; sears